2017
DOI: 10.12659/msm.899547
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Strain Induced Expression of Matrix Metalloproteinase-9 via Stretch-Activated Channels in Rat Abdominal Aortic Dissection

Abstract: BackgroundThe aim of the study was to investigate the expression of matrix metalloproteinase-9 (MMP-9) in rat abdominal aortic dissection (AD) induced by mechanical strain, so as to offer a better understanding of the possible mechanisms of AD.Material/MethodsExperimental AD in rats was achieved by the injection of porcine pancreatic elastase. At days 0, 1, 3, 5, 7, 14, 21, and 30 after the establishment of AD model, serum MMP-9 levels were measured by enzyme-linked immunosorbent assay (ELISA). Four groups of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Stretch-activated channel (SAC) was initially discovered in skeletal muscle cells by Guharay , [ 20 ] and subsequent studies have shown that SAC is widely present in various cell s[ 21 ]. Qiu found that mechanical tension stimulates the SAC signaling pathway and regulates the expression of corresponding mRNAs and proteins in a rat aortic dissection mode l[ 22 ]. The pathophysiological similarity between PH-LHD and aortic dissection is that the vasculature is stimulated by mechanical tension which causes vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Stretch-activated channel (SAC) was initially discovered in skeletal muscle cells by Guharay , [ 20 ] and subsequent studies have shown that SAC is widely present in various cell s[ 21 ]. Qiu found that mechanical tension stimulates the SAC signaling pathway and regulates the expression of corresponding mRNAs and proteins in a rat aortic dissection mode l[ 22 ]. The pathophysiological similarity between PH-LHD and aortic dissection is that the vasculature is stimulated by mechanical tension which causes vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Studies also testified that mechanical stretching can activate the phosphorylation of the MAPK pathway [28,29]. Also, studies have shown that the expression of MMP-9 and TGF-β1 in tissues may be related to stretch-activated channel (SAC) and mitogen-activated protein kinase (MAPK) signaling pathway [12,30,31]. Therefore, we speculated that SAC and MAPK signaling pathway may be potential regulatory molecules in PH-LHD.…”
Section: Introductionmentioning
confidence: 88%
“…Recently, Qiu et al demonstrated that mechanical stretching could up-regulate the expression of MMP-9 in the smooth muscle cells from animals with aortic dissection through SAC/ NF-κB signaling pathway [30]. The mechanical stress of the vascular wall during aortic dissection may influence the structure and function of cells, tissues and organs [44].…”
Section: Plos Onementioning
confidence: 99%
“…The rat aortic rings were collected and intervened by stretch stress according to our previously published study [ 3 ]. Briefly, the aortic vessels were cut into 4 mm ring segments and removed the adventitia and intima.…”
Section: Methodsmentioning
confidence: 99%
“…Aortic dissection (AD) is one of the most dangerous aortic diseases [ 1 ]. Although certain therapeutic benefits have been achieved on the clinical diagnosis and treatment of AD by constantly updated and improved surgical techniques [ 2 ], the mortality and the incidence rate of surgical complications are rising due to unclear pathological mechanism [ 3 ]. The deep investigation on the pathogenesis of AD and the analysis on the prognosis of disease are urgently needed.…”
Section: Introductionmentioning
confidence: 99%